FAKTOR INTERNAL ORGANISASI DAN PENCEGAHAN FRAUD PADA PENGELOLAAN WISATA MANGROVE DI MADURA - Khomsah, Naqibati Rif'atul; Carolina, Anita; Abrori, Rian (Universitas Multimedia Nusantara, 2022)
Abstract”This study aims to identify many factors that can influence fraud prevention in management of mangrove ecotourism in Madura. The population in this study was all management of mangrove ecotourism in Madura. This research uses quantitative methods with several independent variables, namely integrity, organizational culture, accountability and internal control systems, while the dependent variable is fraud prevention. This study uses primary data by distributing questionnaires to pokdarwis's members and managed to obtain 161 respondents. Multiple linear regression analysis is used for data analysis The result indicates that organizational culture and internal control systems have a positive effect on fraud prevention. It is caused by the implementation of transparency through using information boards in tourism management has not been maximized. Different results are obtained in which integrity and accountability have no effect on fraud prevention. Pokdarwis's members are always monitoring and formation of an organizational culture that is aware of fraud prevention actions are the reasons for its influence. Keywords: Integrity; Organizational Culture; Accountability; Internal Control System; Fraud Prevention.